The Effectiveness of Problem-Based Learning and Direct Instruction Models in Enhancing Mathematical Understanding among Elementary School Students - Indriani, Rina; Wahyudin; Turmudi (Mosharafa: Jurnal Pendidikan Matematika, 2023)
Penelitian ini memfokuskan pada perbandingan pengaruh Problem Based Learning (PBL) dan Direct Instruction (DI) terhadap kemampuan pemahaman matematis peserta didik, dengan mempertimbangkan tingkat minat belajar mereka. Desain faktorial 3x2 digunakan, menggabungkan tingkat minat belajar (rendah, sedang, tinggi) dengan model pembelajaran (PBL dan DI). Hasil analisis menunjukkan perbedaan signifikan antara kedua metode pembelajaran, dengan interaksi antara metode dan tingkat minat peserta didik memengaruhi peningkatan pemahaman matematis. Peserta didik dengan minat tinggi cenderung mengalami peningkatan yang lebih signifikan. Temuan ini menekankan pentingnya responsif dan diferensiatif dalam pendekatan pembelajaran matematika, sesuai dengan kebutuhan individual peserta didik. Implikasi praktisnya adalah penyesuaian metode pembelajaran untuk mencapai hasil optimal. Studi ini memperkaya pemahaman tentang hubungan kompleks antara metode pembelajaran, minat belajar, dan pemahaman matematis. This study investigates the comparative impact of Problem-Based Learning (PBL) and Direct Instruction (DI) on students' mathematical understanding, considering their levels of interest in learning. A 3x2 factorial design was employed, incorporating varying levels of learning interest (low, medium, high) and learning models (PBL and DI). Statistical analysis reveals significant distinctions between the two instructional approaches, with the interaction between method and students' interest levels influencing improvements in mathematical understanding. Notably, students with high interest tend to demonstrate more substantial advancements. These findings underscore the importance of adapting instructional strategies to accommodate individualized student needs in mathematics education. The practical implication suggests tailoring teaching methods to optimize educational outcomes. This research enhances our understanding of the intricate dynamics among instructional methods, student interest, and mathematical comprehension.